The Role of Infrastructure Investment on Inclusive Growth and Human Development Index: Evidence from Emerging Economies - Aluko, Timothy O.; Ngubane, Bhekabantu Sifiso (International Journal of Economics and Financial Issues, 2024)
The paper examines the effect of infrastructure investment on the Human Development Index (HDI) score for five middle-income countries, namely Brazil, South Africa, Turkey, Mexico and Vietnam. The dynamic panel data model was used in the study. Data was sourced from the World Bank and the United Nations Development Programme focused on the prevalence and utilisation of five types of infrastructure in the countries mentioned above: electricity, water, sanitation, transport, telecommunications, and schools. The findings show that HDI is too narrow to be used as the main tool to measure human development and suggest that water and sanitation as well as the electrification of households were crucial infrastructures that had a positive impact on the HDI and be viewed as one type of infrastructure when researching the relationship between infrastructure investment and the HDI. The paper concluded and highlighted the need for infrastructure investors and policymakers to have a multi-dimensional approach to measuring the impact they would like to make. In this way, they would have more pronounced insights about which infrastructure they should invest in and how it will improve the wellbeing of society.